Pengaruh Kepemimpinan Transformasional dan Budaya Sekolah Terhadap Kinerja Guru Taman Kanak-kanak - Ashar, Dinar Salasatun; Entoh Tohani (Universitas Pendidikan Ganesha, 2025)
The performance of kindergarten teachers is influenced by various internal school factors, including the leadership style of the principal and the prevailing school culture. Problems arise when weak leadership and an unsupportive school culture result in low teacher performance in carrying out their professional duties. This study aims to analyze the partial and simultaneous effects of transformational leadership and school culture on the performance of kindergarten teachers. This is a quantitative study with an ex post facto design. The research subjects consisted of 234 kindergarten teachers, while the instrument was tested on 33 teachers from a different population. Data collection used a questionnaire in the form of a closed-ended questionnaire that had been tested for validity and reliability. The data analysis techniques used included t-tests, F-tests, and the coefficient of determination (R²). The results of the study indicate that transformational leadership has a significant effect on teacher performance, as does school culture, and that both simultaneously contribute positively to improving kindergarten teacher performance. In conclusion, transformational leadership and school culture are important factors in promoting teachers' professional performance. The implications of this study emphasize the need for school principals to develop an inspirational leadership style and build a positive school culture to create a work environment that supports the improvement of early childhood education quality.